أخطاء القراءة الجهرية باللغة العربية عند الطلبة الناطقين بالملايوية في الجامعة الإسلامية العالمية بماليزيا: دراسة وصفية تحليلية - Khairunnisa binti Bohari (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study approached Arabic reading process from the psycholinguistic standpoint. It aimed at identifying the types of errors in Arabic oral reading committed by Malay-speaking learners, their level of use of the three language cues and the effect of miscues on reading comprehension. The oral reading test, story retelling session and comprehension test were conducted for data collection. The reading miscue analysis which was developed by Goodman, Burke, and Watson (2005) was modified and used to answer the relevant questions. The study involved five Malay female students of Arabic language at the Department of Arabic Language and Literature, International Islamic University Malaysia. They are fourth-year students in Semester 1 of the academic year 2015/2016. The study found that the most common types of reading errors committed were omission, followed by substitution, repetition, intonation, and then insertion. The findings showed that most readers depended extensively on graphophonic cues, and were less efficient in using syntactic cues. Their use of semantic cues was moderate. Reading comprehension scores may not automatically improve, even though the number of oral reading miscues decreased. The low quality miscues did not make sense in the context of the sentence. The study showed that semantic cue had great effect on reading comprehension. The study also revealed that learners have language problems, especially in grammar and vocabulary.